posted by kelli
I don't understand these types of problems-
Find the average rate of change of f between 1 and x
and X cannot be equal to 1
1) f(x)= the square root of x+3
3) f(x)=x^3 + x
Here's how you do #1. The others can be done the same way.
I will assume than f(x) = sqrt(x+3) and not (sqrt x) + 3. You should have used parentheses to clarify the problem.
Find the average rate of change of f between 1 and x . That is
= [sqrt(x+3) - sqrt4]/(x-1)
= [sqrt(x+3) - 2]/x-1)
is the average rate of change in this case, from 1 to x.
For x = 2, this is 0.236..
For x = 3, it is 0.224..
For x = 4, it is 0.215..
For x = 13, it is (4-2)/12 = 0.1667...
Need help I have 91.36 need to round it up to 5 whats my answer